Problems Of Inclusive Education In Indonesia - Amalia Nabila Salim; Disman (International Conference on Elementary Education, 2023)
The application of inclusive education aims to provide convenience related to educational needs for children with special needs who have served in Indonesia for more than ten years. Inclusive education certainly cannot be implemented without obstacles and problems. Many problems arose during the implementation of this inclusive education. The purpose of this article is to explain the implementation of inclusive education in Indonesia. The research method used is qualitative research and library research. Sources of data come from the policy literature and several previous studies on inclusive schools. The results of the study show that there are various problems in implementing inclusive education in Indonesia, such as teacher qualifications, school inclusive education support systems.